Principal Leadership Effect For Teacher Performance With Work Satisfaction Intervening Variable In Jombang - Indrasari, Meithiana; Indyawati, Lilik; Susilo, Daniel (Jurnal Pendidikan Indonesia, 2023)
The principal as the top manager in the school is the most important component which is a determining factor for school success in creating quality human resources in the school environment. The research objectives are: 1) Test the effect of the principal's leadership style on teacher performance; 2) Test the influence of the principal's management on teacher performance; 3) Test the effect of job satisfaction on teacher performance; 4) Test the effect of the principal's leadership style on teacher job satisfaction at Bandarkedungmulyo Jombang State Senior High School; 5) Test the influence of the principal's management on teacher job satisfaction through job satisfaction; 6) Test the significant influence of the principal's leadership style on teacher performance; and 7) Test the significant influence of principal management on teacher performance at Bandarkedungmulyo Jombang Public High School through job satisfaction. The results of the study: 1) Leadership style has a positive and significant influence on teacher performance with a t count > t table (6,746 > 1,674) and a path coefficient of 0.984; 2) Managerial does not have a positive and insignificant effect on teacher performance with a t count < t table (0.206 < 1.674) and a path coefficient of -0.031; 3) Job satisfaction has a positive and significant effect on teacher performance with a t count > t table (2.117 > 1.674) and a path coefficient of 0.383; 4) Leadership Style has a positive and significant influence on Job Satisfaction with a t count > t table (2,850 > 1,674) and a path coefficient of 0.564; 5) Managerial has a positive and significant influence on Job Satisfaction with a t count > t table 1.919 > 1.674) and a path coefficient of 0.583; 6) Leadership Style through Job Satisfaction has a positive and significant influence on Teacher Performance with a t count > t table (5.167 > 1.674) and a path coefficient of 0.092 ; and 7) Managerial through Job Satisfaction has a positive and significant influence on Teacher Performance with a t count > t table (3.178 > 1.679) and a path coefficient of 0.153.